FAKTOR-FAKTOR YANG MEMPENGARUHI PARTISIPASI PETANI DALAM PROGRAM ASURANSI USAHA TANI PADI (AUTP) DI KECAMATAN PENGANDONAN - Maryani Maryani; Munajat Munajat; Yetty Oktarina (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2022)
This study aims to determine the factors that influence farmer participation in the rice farming business insurance program (AUTP) in Pengandonan District. The methodology of this research was carried out with qualitative methods. Where the research uses statistical analysis using logistic regression analysis. Data obtained by distributing questionnaires and data obtained from farmers directly and equipped with secondary data, namely the relevant agencies. The results of this study are the factors that influence farmers' decisions in participating in the rice farming insurance program (AUTP), namely there are seven factors including: age, education, farming experience, land area, income, planting calendar and premiums. Of the seven factors, six factors have a significant effect on farmers' decisions in participating in the rice farming insurance program, namely age, education, farming experience, land area, income, and premiums. And one factor that has no significant effect on farmers' decisions in participating in the rice farming insurance program is the planting calendar factor. Keywords: Participation, insurance, farming, rice